2010
DOI: 10.1245/s10434-009-0887-5
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Marker Evolution: Comparison with Imaging for Assessment of Response to Chemotherapy in Patients with Colorectal Liver Metastases

Abstract: BackgroundAs the real clinical significance of carcinoembryonic antigen (CEA) and carbohydrate antigen 19.9 (CA19.9) evolution during preoperative chemotherapy for colorectal liver metastases (CLM) is still unknown, we explored the correlation between biological and radiological response to chemotherapy, and their comparative impact on outcome after hepatectomy.MethodsAll patients resected for CLM at our hospital between 1990 and 2004 with the following eligibility criteria were included in the study: (1) preo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 28 publications
5
33
0
Order By: Relevance
“…Patients with a larger intrahepatic tumor burden are most at risk for an R1 margin; it is these patients who also have worse overall tumor biology and overall recurrence. To this point, de Haas et al [23] did not find a difference in OS among patients undergoing an R0 vs R1 resection. These data may suggest that, in an era of more effective chemotherapy options, leaving microscopic disease behind may result in increased local failure but not necessarily a worse OS.…”
Section: Surgical Margin Statusmentioning
confidence: 88%
See 2 more Smart Citations
“…Patients with a larger intrahepatic tumor burden are most at risk for an R1 margin; it is these patients who also have worse overall tumor biology and overall recurrence. To this point, de Haas et al [23] did not find a difference in OS among patients undergoing an R0 vs R1 resection. These data may suggest that, in an era of more effective chemotherapy options, leaving microscopic disease behind may result in increased local failure but not necessarily a worse OS.…”
Section: Surgical Margin Statusmentioning
confidence: 88%
“…Among many patients, CEA can be an effective marker to monitor for recurrence, as well as to assess response to systemic therapy [18,21] . CEA levels can correlate with the radiological response to preoperative chemotherapy; however, other data have suggested that the absolute change in CEA level with chemotherapy may not correlate with long-term outcome [23] . As a pre-operative prognostic factor, Mann et al [12] reported that CEA levels did correlate with 5-year survival (CEA levels < 200 ng/mL: 48.9% vs > 200 ng/mL: 0.0%).…”
Section: Preoperative Carcinoembryonic Antigen Levelmentioning
confidence: 91%
See 1 more Smart Citation
“…It is worth mentioning the study of de Haas et al [ 68 ] who evaluated both CEA and CA 19-9 in comparison with the radiological response (TAC) to chemotherapy after complete resection for metastases of CRC, considering a change in levels of at least 20% as significant. Serial determinations of CEA and CA 19-9, respectively, were available for 113 and 68 patients: the patterns of these markers, or biological evolution, was similar to the radiological evidence of response in 94% of cases for CEA and in 91% of cases CA 19-9, and in patients with radiologic progression the correlation with the performance of the serum markers was, respectively, 95% and 64%.…”
Section: Monitoring Of Gastrointestinal Cancersmentioning
confidence: 99%
“…A previous study reported that changes in CEA levels were parallel with radiological tumor responses in frontline chemotherapy in CRC patients with liver-only metastatic disease [33]. On the other hand, recent studies showed that the concordance rate between changes in CEA levels and tumor responses to therapy was only 50-60% in CRC with metastases in various organs [34,35].…”
Section: Discussionmentioning
confidence: 99%